Overproduction, characterization and preliminary antiproliferative activity determination of non-tagged recombinant human interferon alpha-2a produced in Pichia pastoris - NENG HERAWATI; ANDRI WARDIANA; RATIH ASMANA NINGRUM (Nusantara Bioscience, 2017)
Herawati N, Wardiana A, Ningrum RA. 2017. Overproduction, characterization and antiproliferative activity determination of non-tagged recombinant human interferon alpha-2a produced in Pichia pastoris. Nusantara Bioscience 9: 97-101. Recombinant human interferon alpha-2a (rhIFNÎ±-2a) has been widely used for antiviral, anticancer as well as immunomodulatory clinical therapy. In our previous research, we constructed the Open Reading Frame (ORF) encoding synthetic rhIFNÎ±-2a to be in framed with N-terminal alpha factor secretion system in pPICZÎ±B shuttle vector. This research covered overproduction, characterization of the protein and preliminary determination of biological potency assay by using the estrogen positive cell line MCF-7. To overproduce the protein, cultivation was performed in Buffered complex medium containing glycerol (BMGY) for 24 h and production was performed in Buffered complex medium containing methanol (BMMY) during 48 hours at 30Â°C. The recombinant protein was purified by affinity chromatography using blue sepharose resin. Analysis of amino acid sequence by using MS/MS2 mass spectrometry covered 21% of the total amino acid residues. To determine the initial biological activity, the effect of rhIFNÎ±-2a on MCF-7 breast cancer cell line was studied in vitro. The anti-proliferative activity of hIFNÎ±-2a was performed by 3-[4.5-dimethyltiazol-2il]-2.5 diphenylltetrazolium bromide (MTT) assay. The result showed that the protein is able to inhibit MCF-7 proliferation and the reduction of cell growth was dose-dependently. To monitor the protein production, we performed stability expression assay as well. The result informed that the expression of ORF still stable until 60th generation